Self-Disclosure Generasi Z melalui ChatGPT dalam Perspektif Komunikasi Interpersonal - Anisya Yasfa Zahira; Deliya Nur Endah (Journal of Media and Communication | E-ISSN : 3063-9581, 2026)
The development of digital communication technology has changed the way Generation Z establishes and maintains interpersonal relationships. One form of interaction that has increasingly developed is the use of artificial intelligence, particularly ChatGPT, as a digital communication space for expressing thoughts, feelings, experiences, and personal concerns. This phenomenon indicates a tendency toward self-disclosure through artificial intelligence-based media, which is interesting to examine from an interpersonal communication perspective. This study aims to analyze the forms and characteristics of Generation Z's self-disclosure through ChatGPT and to understand the factors that encourage self-disclosure in such interactions. This research employs a qualitative approach with a descriptive method. Data are collected through interviews and documentation involving Generation Z individuals who use ChatGPT as a medium to express their thoughts, feelings, experiences, or personal concerns. Data analysis is conducted through data reduction, data presentation, and conclusion drawing. The findings show that ChatGPT can serve as an alternative space for Generation Z to engage in self-disclosure due to perceived accessibility, communication comfort, and reduced concerns about direct social judgment. From an interpersonal communication perspective, this phenomenon demonstrates that self-disclosure does not only occur through direct human-to-human relationships but can also develop through interaction with artificial intelligence-based communication technology. This study contributes to the expansion of interpersonal communication studies amid the development of digital communication and the increasing use of artificial intelligence.